Fields of Mutual Alignment: A Dual-Order Approach to the Study of Cultural Holes. (September 2017) - Puetz, Kyle
In this article, I discuss how network-analytic exploitations of the duality of agents and social object enable the study of fields from two analytical vantage points. Such an approach entails: (1) the discovery of field positions through identification of cultural holes within a network of agents' tastes and (2) the measurement of interobject competition to identify social objects contributing most to the organization of field positions. Characterizing this approach as a mutual-alignment framework, I discuss its analytical advantages. At the level of the agent, I suggest that positions within fields retrieve their value by virtue of their relational style, or their relationship to the field's cultural holes. At the level of the social object, I provide an analytical framework for identifying structurally important social objects through relationships of asymmetrical competition and incommensurability, or a lack of substitutability. I provide an empirical application to a population of film critics.